Zimbabwe : Request for Targeted Lifting of the Suspension of Fund Technical Assistance. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses Zimbabwe's request for targeted lifting of the suspension of fund technical assistance. Zimbabwe's cooperation on payments has remained poor: during the period April 2008-March 2009, the IMF received SDR 0.3 million. The government's forward-looking policy intentions are sound, but their success mainly depends on the authorities' ability to sustain political commitment and to strengthen technical capacity. The Zimbabwe authorities have expressed their commitment to improve cooperation on payments to the IMF.